Kapasitas Pengembangan Sumber Daya Manusia Aparatur pada Badan Kepegawaian Kabupaten Luwu - Dewata, Dewata; Rahman, Rahman; Hasran, Hasran; Akhmad, Zaenal (Journal of Government Insight, 2023)
The study aim for know factors influence implementation development capacity Source Power Man Apparatus at the Luwu Regency Civil Service Agency. Study This held in region Regency Luwu with focus on Body Staffing Regency Luwu And In this research the author uses the descriptive type, Basic study is a survey. In study used technique data collection with method : Literature study (library research), Observation, Interview, namely interview direct with respondents who have determined, and Questionnaire. Population in study This is all over apparatus government Regency Luwuk is there on Luwu Regency Civil Service Agency . Sample In study This taken 3 Assistants, Head Part 12, Head Sexy 34 people with use technique purposive sampling. Data analysis for obtain description about condition every variable in a way single thing done with table frequency with analysis descriptive with determine range scale. The research results show that there are factors that influence the implementation of Human Resources development apparatus is a low level of understanding of Work Systems and Procedures, a lack of budget allocation, and facilities and infrastructure that are still lacking.